2019
DOI: 10.24180/ijaws.536754
|View full text |Cite
|
Sign up to set email alerts
|

Domateste Salisilik Asit Uygulamasıyla Soğukta Depolama Süresince Kalite Kayıplarının Azaltılması

Abstract: Çalışma, derim sonrası salisilik asit (SA) ile muamele olmuş Anıt F1 domates çeşidinin soğukta muhafaza süresince meyve kalitesinde meydana gelen değişimi belirlemek amacı ile yürütülmüştür. Bu amaçla ticari derim döneminde toplanan domatesler, farklı dozlarda SA+Tween 20 [0 (kontrol), 0.5, 1 ve 2 mM] içeren çözeltiye 10 dak süre ile daldırılmıştır. Daha sonra meyveler karton kutulara yerleştirilmiştir. Ambalajlanmış domatesler 8 °C'de %90±5 oransal nem koşullarında 25 gün depolanmış ve 5 gün aralıklarla bazı … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…In studies conducted on tomato (Akbulut, 2015) and pepper (Gülsoylu, 2015), soluble solid content in SA treatments was found to be higher than in the control at the end of the storage period. Davras et al (2019) and Üner (2021) reported that no significant difference was observed between control and SA applications in terms of soluble solid content in tomato and parsley during storage.…”
Section: Changes In Wl Dry Matter Ash Tss and Ph Contentsmentioning
confidence: 99%
See 3 more Smart Citations
“…In studies conducted on tomato (Akbulut, 2015) and pepper (Gülsoylu, 2015), soluble solid content in SA treatments was found to be higher than in the control at the end of the storage period. Davras et al (2019) and Üner (2021) reported that no significant difference was observed between control and SA applications in terms of soluble solid content in tomato and parsley during storage.…”
Section: Changes In Wl Dry Matter Ash Tss and Ph Contentsmentioning
confidence: 99%
“…Alali et al (2023) reported that CA has the ability to close stomata, reduce transpiration rates, and decrease WL in fruits and vegetables. In studies conducted on cucumber (Altıkardeş et al, 2018), tomato (Davras et al, 2019) and parsley (Üner, 2021), it was determined that postharvest SA applications significantly reduced WL at the end of the storage period compared to the control.…”
Section: Changes In Wl Dry Matter Ash Tss and Ph Contentsmentioning
confidence: 99%
See 2 more Smart Citations